Impact of Wide-Ranging Nanoscale Chemistry on Band Structure at Cu(In, Ga)Se2 Grain Boundaries. Issue 1 (December 2017) - Stokes, Adam; Al-Jassim, Mowafak; Diercks, David; Clarke, Amy; Gorman, Brian
Abstract The relative chemistry from grain interiors to grain boundaries help explain why grain boundaries may be beneficial, detrimental or benign towards device performance. 3D Nanoscale chemical analysis extracted from atom probe tomography (APT) (10's of parts-per-million chemical sensitivity and sub-nanometer spatial resolution) of twenty grain boundaries in a high-efficiency Cu(In, Ga)Se2 solar cell shows the matrix and alkali concentrations are wide-ranging. The concentration profiles are then related to band structure which provide a unique insight into grain boundary electrical performance. Fluctuating Cu, In and Ga concentrations result in a wide distribution of potential barriers at the valence band maximum (VBM) (−10 to −160 meV) and the conduction band minimum (CBM) (−20 to −70 meV). Furthermore, Na and K segregation is not correlated to hampering donors, (In, Ga)Cu and VSe, contrary to what has been previously reported. In addition, Na and K are predicted to be n-type dopants at grain boundaries. An overall band structure at grain boundaries is presented.